Diversity of fungal species and decomposition of Rhizophora mucronata leaf litter in the Deli Belawan River Estuary, North Sumatra, Indonesia - YUNASFI YUNASFI; SRI RUSMAYANTI LUBIS; BUDI UTOMO; AFIFUDDIN DALIMUNTHE; VINANSIA M. SIHOTANG; SEPHIA SEMBIRING; GLOURY ARIZONA SITEPU; JON GANDA MARPAUNG PURBA; RICKSON SILALAHI; IPANNA ENGGAR SUSETYA; AMANATUL FADHILAH; ZULHERI NOER (Society for Indonesian Biodiversity, 2025)
Abstract. Yunasfi, Lubis SR, Utomo B, Dalimunthe A, Sihotang VM, Sembiring S, Sitepu GA, Purba JGM, Silalahi R, Susetya IE, Fadhilah A, Noer Z. 2025. Diversity of fungal species and decomposition of Rhizophora mucronata leaf litter in the Deli Belawan River Estuary, North Sumatra, Indonesia. Biodiversitas 26: 1631-1640. Rhizophora mucronata is one of the most widely known mangrove species, growing in coastal areas, such as along river estuaries, deltas, and lagoons. This species produces leaf litter that is useful for organisms living in mangrove water after decomposition. The decomposition of R. mucronata leaf litter is often affected by the presence of salinity in seawater including other environmental factors such as pH, humidity, rainfall, temperature, and river current speed. Fungi played an important role in the process of litter decomposition by facilitating the degradation of organic compounds such as cellulose and lignin which are components of leaf cell walls. The aim of this study was to determine the fungal species diversity and decomposition of R. mucronata leaf litter at salinity levels of 0-10 ppt in the Belawan Deli River. The study used 24 bags of 40 × 30 cm litter bags. Fungal isolation was carried out using the dilution method to calculate the number of fungal colonies in R. mucronata leaf litter. Furthermore, the analysis of carbohydrate and protein contents in R. mucronata leaf litter was carried out using the semi-micro method (01-2891-1992 SNI). The results of isolation showed that species of fungi were associated with R. mucronata leaf litter, namely Aspergillus sp.1, Aspergillus sp. 2, Aspergillus sp. 3, Penicillium sp., Trichoderma sp. The decomposition rate of R. mucronata leaf litter was 0.018/year. The average percentage of total carbohydrates and proteins was 9.33 and 5.54%, respectively. Based on the outcomes found in this research, the author suggested to conduct research on R. mucronata leaf litter at salinity levels of 11-20 ppt and 21-30 ppt to further observe the diversity of fungal species.